1999
DOI: 10.1590/s0006-87051999000100001
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of malate dehydrogenase in wild pepper

Abstract: Leaf extracts from wild pepper (Capsicum flexuosum Sendt) were analysed for the presence of malate dehydrogenase (E.C. 1.1.1.37; MDH) isozymes using starch gel electrophoresis. Seven phenotypes for MDH isozymes were observed in the genitors. Genetic analysis in F 1 progenies revealed five loci coding for MDH. Isozyme banding patterns of hybrids indicated that MDH-3 and MDH-4 genes code for monomeric enzymes, while MDH-5 for a dimeric isoform. In MDH-2 loci, one particular F 1 progeny showed a significant devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…Suso et al (2005) have shown that yield and out crossing of legume depend greatly on floral design and display. For years agronomic and morphological characteristic descriptions have been used to differentiate genetic diversity in plants (Schuelter et al, 1999). With the advance of sciences, more efficient tools were adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Suso et al (2005) have shown that yield and out crossing of legume depend greatly on floral design and display. For years agronomic and morphological characteristic descriptions have been used to differentiate genetic diversity in plants (Schuelter et al, 1999). With the advance of sciences, more efficient tools were adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Como não se detectou a presença de bandas polimórficas, separaram-se as bandas em quatro regiões, porém sem poder concluir quanto à segregação. Em estudo realizado por Schuelter et al (1999) para Capsicum flexuosum, foi detectada a presença de cinco regiões, sendo possível verificar tanto a presença de enzimas monoméricas como de diméricas. Mcmillin & Scandalious (1981) detectaram em milho a presença de três locos gênicos que segregam independentemente, e que são denominados Mdh1, Mdh2 e Mdh3.…”
Section: Análise Estatística Dos Marcadores Isoenzimáticos E Rapdunclassified